Komparativna analiza nivoa folata u plazmi, homocisteina i eritrocita folata kod trudnica nakon primene folne kiseline tokom različitih trudnoća: Comparison of Folate and Homocysteine in Pregnancies - Jin, Xinglin; Meng, Mei; Wang, Xi (Journal of Medical Biochemistry, 2024)
Background: To examine and evaluate the alterations in plasma folate, homocysteine (HCY), and erythrocyte folate (FOA) concentrations among expectant mothers following folic acid supplementation in distinct pregnancies.Methods: A retrospective analysis was conducted on clinical data from 416 pregnant women admitted to our hospital between October 2020 and October 2023. These women were selected as the subjects of observation and divided into two groups based on their folic acid intake duration: an observation group (n=210) who consumed folic acid before and during early pregnancy, and continued taking it throughout mid and late pregnancy (≥ 20 days per month), and a control group (n=206) who took folic acid before and during early pregnancy but did not continue taking it in mid and late pregnancy (≥ 20 days per month). The prenatal levels of folate, HCY, and FOA were compared among the different groups of pregnant women. Pearson correlation analysis was used to explore the relationship between changes in folate, HCY, and FOA levels in pregnant women. Moreover, the fasting blood glucose (FBG) and 2-hour postprandial blood glucose (P2BG) levels were compared between the two groups of pregnant women. The incidence of gestational diabetes (GDM), gestational hypertension (HIP), and gestational anemia were also compared. Additionally, comparisons were made regarding the changes in delivery mode, newborn height, weight, head circumference, and chest circumference between the two groups of pregnant women.Results: The control group exhibited significantly lower levels of plasma folate and FOA compared to the observation group, while the levels of HCY were significantly higher in the control group than in the observation group, with statistically significant differences (P